Composite water-based polymer binder with strong self-healing property prepared based on hydrogen-bond interaction, preparation method and application in lithium ion battery

By using the composite aqueous polymer binder PAA/APBIA-PI prepared based on hydrogen bonding in lithium-ion batteries, the problem of mechanical bonding strength reduction caused by volume expansion during lithiation of silicon-based electrodes is solved, and higher circulation capacity and stability are achieved.

CN119614139APending Publication Date: 2025-03-14INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411705206.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, volume expansion of silicon-based electrodes during lithiation leads to reduced mechanical bonding strength and insufficient cycling performance and stability.

Method used

The composite aqueous polymer binder PAA/APBIA-PI prepared based on hydrogen bonding is formed by blending acid polyacrylic acid (PAA) and imidazole group-containing water-soluble polyimide (APBIA-PI), to establish a reversible physical crosslinking network to improve the mechanical bonding strength of the electrode.

Benefits of technology

It significantly improves the mechanical bonding strength of silicon-based electrodes and the circulation capacity and stability of the battery, and is suitable for use under different working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614139A_ABST
    Figure CN119614139A_ABST
Patent Text Reader

Abstract

The invention provides a strong self-healing composite water-based polymer binder prepared based on hydrogen-bond interaction, a preparation method and application in a lithium ion battery, the binder is formed by blending commercial polyacrylic acid (PAA) and imidazolyl-containing water-soluble polyimide (APBIA-PI), PAA has rich acidic carboxyl groups, and the polymer binder has good self-healing property, and has good self-healing property. The alkaline imidazole group of the APBIA-PI can interact with the alkaline imidazole group of the APBIA-PI to form a three-dimensional network physical cross-linked network, and the cross-linked form has reversibility and can be recovered after large-volume expansion; and by optimizing the ratio of PAA to APBIA-PI, the cohesiveness and functionality of the polymer binder can be adjusted, and the polymer binder is suitable for being used under different working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite water-based polymer binder with strong self-healing property prepared based on hydrogen bonding, a preparation method and application in lithium ion batteries. Background Art

[0002] Burning fossil fuels to power cars, generate electricity and operate factories has been identified as a major cause of global warming. Reducing the rate at which fossil fuels are burned requires the production of energy-efficient devices, such as electric vehicles, but such products rely on systems that can store large amounts of energy, which in turn continues to increase the demand for lithium-ion batteries (LIBs) with increasingly higher energy densities [Nature 2008, 451, 652~657].

[0003] To meet this demand, it is necessary to replace the traditional carbon-based negative electrode materials with the next generation of negative electrode materials with higher energy capacity. So far, people have studied a variety of negative electrode materials, such as hard / soft carbon including graphene [Adv.Funct. Mater. 2005, 15, 547~556], lithium alloys (Si, Sn, Al, Sb, etc.) [Science 2011, 334,75~79], transition metal oxides (CoO, Co 3 O 4 、MnO 2 、MoO 3 、TiO 2 etc.) [Adv. Mater. 2012, 24, 5762~5766], and chromium compounds [J. Mater. Chem. A 2014, 2, 4551~4557], in order to improve the energy density of LIB. Among them, silicon-based anodes have a very high theoretical capacity (4200 mAh g -1 , Li 4.4 Si, low cost, benign environmental impact and abundant natural resources are considered to be the most promising alternative to lithium battery anodes. However, silicon-based electrodes undergo a volume change of up to 300% during lithiation (alloying), which may cause the silicon active material to break and fall off the copper current collector, resulting in loss of electrical contact, increased internal resistance and loss of active materials, which seriously reduces the cycle performance [Nat. Nanotechnol. 2014, 9, 187~192].

[0004] Recently, many researchers in the field of battery technology have shown great interest in the study of polymer binders, as polymer binders are simple and low-cost materials that can accommodate the volume expansion of silicon-based electrodes. - In addition to the traditional poly(vinylidene fluoride) (PVDF), polymer binders with carboxyl groups such as poly(acrylic acid) (PAA) [ACS Appl. Mater. Interfaces 2010, 2, 3004~3010], carboxymethyl cellulose (CMC) [J. Power Sources 2006, 161,617~622.], alginate and polysaccharides [Energy Environ. Sci. 2015, 8, 1224~1230.] are also considered to be able to improve the capacity retention of silicon-based electrodes. The use of these binders can improve the cycle life, which is attributed to the formation of a certain degree of self-crosslinking anhydride network during the electrode preparation process, coupled with the binding between the functional groups (carboxyl groups) of the binder polymer and the partially hydrolyzed surface of the silica layer of the silicon particles.

[0005] Chemical crosslinking of alginate [Chem. Commun. 2014, 50, 6386~6389], acidic [Angew. Chem., Int.Ed. 2012, 51, 8762~8767], ionic [Adv. Mater. 2014, 26, 7979~7985] and hyperbranched polymer binders [Nano Lett. 2014, 14, 864~870] has also been considered as a method to improve the stability of silicon-based electrode LIBs. However, although three-dimensionally interconnected chemically crosslinked polymers exhibit high strain resistance and irreversible deformation capacity due to the strong interactions between polymer chains, the nature of chemical crosslinking also increases the stability of the polymer network, resulting in the gradual irreversible breakage of the network [J. Am. Chem. Soc. 2002, 124,2100~2101], which leads to the ultimate degradation of battery performance during long-term operation.

[0006] Here, this patent proposes a new type of polymer binder whose electrostatic crosslinking is induced by the reversible interaction between acidic polyacrylic acid and alkaline imidazole-containing aqueous polyimide (APBIA-PI). APBIA-PI is an aromatic macromolecule with a large number of imidazole groups in the polymer backbone. The imidazole group has donor and acceptor hydrogen bonding sites that can participate in specific interactions and produce imidazole carboxyl groups after reaction with polyacrylic acid (PAA). Studies have shown that PAA / APBIA-PI mixed binders can give silicon composite electrodes high mechanical bonding strength on silicon, which can significantly improve battery performance compared to electrodes based only on PAA. Summary of the invention

[0007] The purpose of the present invention is to provide a composite water-based polymer binder with strong self-healing properties prepared based on hydrogen bonding, a preparation method and application in lithium-ion batteries. The binder is a new type of composite binder (PAA / APBIA-PI) based on physical cross-linking, which is formed by simple blending of commercial polyacrylic acid (PAA) and water-soluble polyimide containing imidazole groups (APBIA-PI), and has excellent bonding properties.

[0008] The present invention proposes a water-based polymer binder with physical crosslinking induced by hydrogen bonding, which is formed by blending commercial polyacrylic acid (PAA) and water-soluble polyimide containing imidazole groups (APBIA-PI). PAA has abundant acidic carboxyl groups and can interact with the basic imidazole groups of APBIA-PI to form a three-dimensional network of physical crosslinking. This crosslinking form is reversible and can be restored after a large volume expansion. By optimizing the ratio of PAA and APBIA-PI, the adhesion and functionality of the polymer binder can be adjusted, making it suitable for use under different working conditions.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A composite water-based polymer binder with strong self-healing properties prepared based on hydrogen bonding. The binder is prepared based on hydrogen bonding, and its raw materials include water-soluble polyimide (APBIA-PI) with a benzimidazole structure and polyacrylic acid (PAA). Through mechanical blending of PAA and APBIA-PI, a composite polymer binder PAA / APBIA-PI with reversible physical cross-linking can be formed.

[0011] Furthermore, the commercially available polyacrylic acid (PAA) used in the present invention comprises a homopolymer of the following repeating units:

[0012]

[0013] Wherein, n is not less than 10. Polyacrylic acid (PAA), which has a large number of carboxylic acid groups (on average, 1g of polymer molecules has more than 13.88 mmol of carboxylic acid groups), provides sites for interaction with imidazole; the weight average molecular weight of polyacrylic acid is not less than 10,000 and not more than 1,000,000, for example, the weight average molecular weight is 45,000.

[0014] Furthermore, the water-soluble polyimide (APBIA-PI) with a benzimidazole structure in the present invention is copolymerized by 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA), other diamine monomers (B), dianhydride monomers (A) and imidazole organic compounds (M). The specific structure of the water-soluble polyimide (APBIA-PI) with a benzimidazole structure is: a copolymer containing the following repeating structural units:

[0015]

[0016] Wherein, x+y=1, 0≤x≤1, 0≤y≤1; for example, x is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1. For example, y is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1;

[0017] A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group; for example, A is a residue derived from a dianhydride monomer, and A is at least one of the following structures:

[0018]

[0019] B represents at least one of the following groups: a divalent organic group of an aromatic diamine without fluorine, whose solubility in water is greater than 0.1 g / L (25°C) and does not contain an amino group; a divalent organic group of an aliphatic diamine, whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is a residue derived from a diamine monomer, and B is at least one of the following structures:

[0020]

[0021] M is an imidazole organic compound, which reacts with the carboxyl group of polyamic acid to form a water-soluble polyamic acid salt, and its characteristics are as follows:

[0022]

[0023] Among them, X 1 To X 4 represents a hydrogen atom or an alkane group having less than 5 carbon atoms.

[0024] The present invention also provides a method for preparing a composite water-based polymer binder with strong self-healing properties based on hydrogen bonding. In the present invention, PAA and APBIA-PI are mechanically blended to form a composite polymer binder PAA / APBIA-PI with reversible physical crosslinking, which comprises the following steps:

[0025] (1) At room temperature, firstly dissolve one or more of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and a diamine monomer containing a B group in deionized water, then add at least one of the imidazole organic compounds M to the solution, stir for at least 1 hour, and prepare a transparent solution, then add a dianhydride monomer containing an A group and dissolve it in the aforementioned solution, wherein the molar ratio of the dianhydride monomer to the diamine monomer is 0.9-1.3:1 (for example, the molar ratio of the dianhydride monomer to the diamine monomer is 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.0 5:1, 1.07:1, 1.09:1, 1:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1 or 1.3:1, the solution concentration is controlled at 10-30wt% (for example, 10wt%, 15wt%, 20wt%, 25wt%, 28wt% or 30wt%), and the molar ratio of the imidazole organic compound M to the dianhydride monomer containing the A group is 2.5 or more (for example, the molar ratio of the imidazole organic compound M to the dianhydride monomer containing the A group is 2.5, 2.6, 2.8, 3, 3.2, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10);

[0026] (2) Under an inert gas environment, the mixture in (1) is reacted for at least 6 hours to obtain a product having a certain viscosity (greater than 100 mPa at 25°C). s) a precursor solution of an aqueous imidazole-containing polyimide (APBIA-PI);

[0027] (3) Dissolving the APBIA-PI precursor solution and PAA in deionized water at room temperature and mechanically stirring for at least 1 h to obtain a PAA / APBIA-PI precursor solution;

[0028] (4) Under vacuum conditions, the obtained PAA / APBIA-PI precursor solution is treated at high temperature (>100° C.) for at least 30 minutes to obtain the composite aqueous polymer binder (PAA / APBIA-PI).

[0029] For example, in step (1), the dianhydride monomer containing the A group is at least one of the following structures:

[0030] For example, in step (1), the diamine monomer containing a B group is at least one of the following structures:

[0031]

[0032] For example, in step (1), M is an imidazole organic compound, which reacts with the carboxyl group of the polyamic acid to form a water-soluble polyamic acid salt, the structural formula of which is as follows:

[0033]

[0034] Among them, X 1 To X 4 represents a hydrogen atom or an alkane group having less than 5 carbon atoms (e.g., 1 carbon atom, 2 carbon atoms, 3 carbon atoms or 4 carbon atoms), respectively.

[0035] The present invention also provides an application of a composite water-based polymer binder with strong self-healing properties prepared based on hydrogen bonding. The PAA / APBIA-PI precursor solution obtained by the present invention is used as an electrode binder in a lithium-ion battery, comprising the following steps:

[0036] 1) Electrode manufacturing step: dissolving the negative electrode active material (including but not limited to silicon, graphite or silicon-carbon composite material, etc.), conductive agent, and polyimide precursor solution in deionized water in a certain proportion, mixing them evenly using magnetic stirring and ultrasonic waves, and coating the slurry evenly on one side of the current collector using a coating preparation device; here, the solid content of the PAA / APBIA-PI precursor solution is higher than 1wt%, and the negative electrode active material loading is greater than 0.2mg·cm -2 ;

[0037] 2) The coated electrode is placed in a forced air oven at 60°C for 1-3 hours and then transferred to a vacuum oven for treatment at a higher temperature (>100°C) for 0.5-12 hours to complete the preparation of the electrode with PAA / APBIA-PI as a binder;

[0038] 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-12 mm on a manual slicer. The mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating;

[0039] 4) Complete the installation of the lithium-ion battery buckle.

[0040] The present invention also provides another application of a composite water-based polymer binder with strong self-healing properties prepared based on hydrogen bonding. The PAA / APBIA-PI precursor solution obtained by the present invention is used for a polyimide film, and the preparation method thereof comprises the following steps:

[0041] 1) The obtained PAA / APBIA-PI precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 60-100°C for 5-24h to form a film, and then vacuum dried at 80-120°C for 5-24h, and vacuum treated at 150°C-350°C for 1-12h to complete the imidization process, thereby obtaining a PAA / APBIA-PI composite polymer film.

[0042] The beneficial results of the present invention are:

[0043] (1) The present invention discloses a composite polymer PAA / APBIA-PI that is solvent-free, has excellent adhesion and good self-healing properties, and is physically cross-linked by hydrogen bonding.

[0044] (2) A composite polymer film is prepared from the precursor solution of PAA / APBIA-PI in (1) above, which has good tensile strength and flexibility, with a tensile strength of 50-200 MPa and an elongation at break of 10-150%;

[0045] (3) The composite polymer prepared from the precursor solution of PAA / APBIA-PI in (1) above has excellent thermal stability, and the polymer decomposition temperature can reach 200-500°C;

[0046] (4) The precursor solution of PAA / APBIA-PI in (1) above is used to prepare a negative electrode binder for lithium-ion batteries. The binder is applied to lithium-ion batteries, and the batteries have excellent cycle capacity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the cycle performance curve of the silicon negative electrode prepared in Example 1 in the lithium-ion battery testing device.

[0048] Figure 2 This is the rate performance curve of the silicon negative electrode prepared in Example 1 in the lithium-ion battery testing device. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is described in detail below through specific embodiments, but it should be clearly stated that these embodiments are for illustration and are not to be construed as limiting the scope of the present invention.

[0050] Example 1:

[0051] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, first dissolve p-phenylenediamine (PDA) (9.73 g, 0.09 mol) and 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) (2.24 g, 0.01 mol) in deionized water (232 g), then add 1,2-dimethylimidazole (DMIZ) (24.03 g, 0.25 mol) and mechanically stir at 25 °C for 1 h to prepare a transparent solution. Then add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) monomer (29.42 g, 0.1 mol) and dissolve it in the above solution. Mechanically stir at 70 °C for 18 h to obtain APBIA. 10 -PI precursor solution, the solid content of the solution is 15 wt %;

[0052] (2) In a 20 mL flat-mouth glass bottle, add the APBIA 10 -PI precursor solution (3.0 g) and polyacrylic acid (PAA) (0.05 g) (weight average molecular weight is 450,000, and 1 g of polyacrylic acid molecule has 13.88 mmol of carboxylic acid groups) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 10 -PI (10:90) composite polymer precursor solution;

[0053] (3) Obtained PAA / APBIA 10 The precursor solution of the -PI (10:90) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 6 hours, then vacuum treated at 120°C for 1 hour, and vacuum treated at 200°C for 30 minutes to complete the heat treatment process, and PAA / APBIA was obtained. 10 -PI (10:90) composite polymer film (50um);

[0054] (4) Table 1 summarizes PAA / APBIA 10 -PI (10:90) composite polymer precursor solutions and film properties.

[0055] PAA / APBIA of the present invention 10 -PI (10:90) composite polymer applications include:

[0056] The obtained composite polymer is used as a polymer binder for a lithium ion battery device, comprising the following steps:

[0057] 1) Prepare the silicon negative electrode of the lithium-ion battery. The negative electrode is prepared as follows: the precursor solution of the composite polymer is mixed with deionized water, conductive carbon black (TIMCAL, Super C45), and nano silicon (Canrd, 80-100nm) in a mass ratio of 10:10:80, and magnetic stirring is performed for 12-24 hours. After ultrasonic treatment for 30 minutes, the obtained slurry is coated on a copper foil with a scraper (the coating thickness is 100um). The prepared electrode is dried at 60°C for 1 hour, and then vacuum treated at 150°C for 6 hours to obtain a silicon negative electrode sheet;

[0058] 2) The current collector after solvent drying was made into a circular electrode sheet with a diameter of 12 mm on a manual slicer. The mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating; the loading amount of active material was controlled at 1.2 mg / cm 2 ;

[0059] 3) All battery assemblies were carried out in an argon atmosphere glove box, and the water and oxygen content in the glove box was less than 0.1 ppm. The prepared electrode sheet was used as the working electrode, the metal lithium sheet was used as the negative electrode, and a 1.0 M / L lithium hexafluorophosphate (LiPF 6 ), a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 and a 10% volume ratio of fluoroethylene carbonate (FEC) additive as the electrolyte, according to Figure 1 After the packaged button cell is left to stand for 12 hours, the cycle performance test can be carried out: after 2 cycles of activation at 1.0A / g, the test starts at 4.2A / g and the temperature is 25°C.

[0060] Figure 1 The cycling performance curve of the binder prepared for Example 1 and applied to the silicon-based half-cell was tested at 25°C. After 2 cycles of charge and discharge at 1.0 A / g, the battery was charged and discharged for 100 cycles at a high current density of 4.2 A / g. Even at a high current density of 4.2 A / g, the battery still had excellent cycle capacity and stability: after 100 cycles of charge and discharge, the battery still had a high capacity of 1923 mAh / g and a capacity retention rate of 59.5%.

[0061] Figure 2The rate performance curve of the binder prepared in Example 1 and applied to the silicon-based half-cell was tested at 25°C and cycled 10 times at current densities of 0.5 A / g, 1 A / g, 2 A / g, 4 A / g, 8 A / g, 12 A / g, and 2 A / g, respectively; the half-cell prepared using the binder can maintain a capacity of 1646 mAh / g at a high current density of 12 A / g, and after recovering to a low current density of 2.0 A / g and cycling 10 times, it still has a high capacity of 2809 mAh / g. Therefore, the binder applied to the silicon-based half-cell in Example 1 has excellent rate performance.

[0062] Example 2:

[0063] (1) In a 20 mL flat glass bottle, place the APBIA 10 -PI precursor solution (2.33 g) and PAA (0.15 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 10 -PI (30:70) composite polymer precursor solution;

[0064] (2) Obtained PAA / APBIA 10 The precursor solution of the -PI (30:70) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature, treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 10 -PI (30:70) composite polymer film (50um);

[0065] (3) Table 1 summarizes PAA / APBIA 10 Properties of precursor solutions and films of the PI (30:70) composite polymers.

[0066] The remaining application steps are the same as Example 1.

[0067] Example 3:

[0068] (1) In a 20 mL flat glass bottle, place the APBIA 10 -PI precursor solution (1.67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 10 -PI (50:50) composite polymer precursor solution;

[0069] (2) Obtained PAA / APBIA 10The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 10 -PI (50:50) composite polymer film (50um);

[0070] (3) Table 1 summarizes PAA / APBIA 10 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0071] The remaining application steps are the same as Example 1.

[0072] Example 4:

[0073] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, firstly, PDA (8.65 g, 0.08 mol) and APBIA (4.48 g, 0.02 mol) were dissolved in deionized water (241 g), and then DMIZ (24.03 g, 0.25 mol) was added and mechanically stirred at 25 °C for 1 h to prepare a transparent solution. Then, BPDA monomer (29.42 g, 0.1 mol) was added and dissolved in the above solution and mechanically stirred at 70 °C for 18 h to obtain APBIA. 20 -PI precursor solution, the solid content of the solution is 15wt%;

[0074] (2) In a 20 mL flat-mouth glass bottle, add the APBIA 20 -PI precursor solution (3.0 g) and PAA (0.05 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 20 -PI (10:90) composite polymer precursor solution;

[0075] (3) Obtained PAA / APBIA 20 The precursor solution of the -PI (10:90) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 20 -PI (10:90) composite polymer film (50um);

[0076] (4) Table 1 summarizes PAA / APBIA 20 -PI (10:90) composite polymer precursor solutions and film properties.

[0077] The remaining application steps are the same as Example 1.

[0078] Example 5:

[0079] (1) In a 20 mL flat glass bottle, place the APBIA 20 -PI precursor solution (2.33 g) and PAA (0.15 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 20 -PI (30:70) composite polymer precursor solution;

[0080] (2) Obtained PAA / APBIA 20 The precursor solution of the -PI (30:70) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature, treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 20 -PI (30:70) composite polymer film (50um);

[0081] (3) Table 1 summarizes PAA / APBIA 20 Properties of precursor solutions and films of the PI (30:70) composite polymers.

[0082] The remaining application steps are the same as Example 1.

[0083] Example 6:

[0084] (1) In a 20 mL flat glass bottle, place the APBIA 20 -PI precursor solution (1.67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 20 -PI (50:50) composite polymer precursor solution;

[0085] (2) Obtained PAA / APBIA 20 The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 20 -PI (50:50) composite polymer film;

[0086] (3) Table 1 summarizes PAA / APBIA 20 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0087] The remaining application steps are the same as Example 1.

[0088] Example 7:

[0089] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, firstly, PDA (6.49 g, 0.06 mol) and APBIA (8.97 g, 0.04 mol) were dissolved in deionized water (254 g), and then DMIZ (24.03 g, 0.25 mol) was added and mechanically stirred at 25 °C for 1 h to prepare a transparent solution. Then, BPDA monomer (29.42 g, 0.1 mol) was added and dissolved in the above solution and mechanically stirred at 70 °C for 18 h to obtain APBIA. 40 -PI precursor solution, the solid content of the solution is 15wt%;

[0090] (2) In a 20 mL flat-mouth glass bottle, add the APBIA 40 -PI precursor solution (3.00 g) and PAA (0.05 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 40 -PI (10:90) composite polymer precursor solution;

[0091] (3) Obtained PAA / APBIA 40 The precursor solution of the -PI (10:90) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 40 -PI (10:90) composite polymer film;

[0092] (4) Table 1 summarizes PAA / APBIA 40 -PI (10:90) composite polymer precursor solutions and film properties.

[0093] The remaining application steps are the same as Example 1.

[0094] Example 8:

[0095] (1) In a 20 mL flat glass bottle, place the APBIA 40 -PI precursor solution (2.33) and PAA (0.15 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 40 -PI (30:70) composite polymer precursor solution;

[0096] (2) Obtained PAA / APBIA 40 The precursor solution of the -PI (30:70) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature, treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 40 -PI (30:70) composite polymer film (50um);

[0097] (3) Table 1 summarizes PAA / APBIA 40 Properties of precursor solutions and films of the PI (30:70) composite polymers.

[0098] The remaining application steps are the same as Example 1.

[0099] Example 9:

[0100] (1) In a 20 mL flat glass bottle, place the APBIA 40 -PI precursor solution 1.67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / APBIA 40 -PI (50:50) composite polymer precursor solution;

[0101] (2) Obtained PAA / APBIA 40 The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / APBIA. 40 -PI (50:50) composite polymer film;

[0102] (3) Table 1 summarizes PAA / APBIA 40 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0103] The remaining application steps are the same as Example 1.

[0104] Example 10:

[0105] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, first dissolve p-PDA (8.65 g, 0.08 mol) and APBIA (4.48 g, 0.02 mol) in deionized water (250 g), then add DMIZ (24.03 g, 0.25 mol) and mechanically stir at 25 °C for 1 h to prepare a transparent solution. Then add 4,4'-oxydiphthalic anhydride (ODPA) monomer (31.02 g, 0.1 mol) and dissolve it in the above solution. Mechanically stir at 70 °C for 18 h to obtain ODPA-APBIA 20 -PI precursor solution, the solid content of the solution is 15 wt %;

[0106] (2) In a 20 mL flat-mouth glass bottle, add the ODPA-APBIA obtained in (1) above. 20 -PI precursor solution (1.67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / ODPA-APBIA 20 -PI (50:50) composite polymer precursor solution;

[0107] (3) The obtained PAA / ODPA-APBIA 20 The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / ODPA-APBIA. 20 -PI (50:50) composite polymer film (50um);

[0108] (4) Table 1 summarizes the PAA / ODPA-APBIA 20 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0109] The remaining application steps are the same as Example 1.

[0110] Example 11:

[0111] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, firstly, p-PDA (8.65 g, 0.08 mol) and APBIA (4.48 g, 0.02 mol) were dissolved in deionized water (256 g), and then DMIZ (24.03 g, 0.25 mol) was added and mechanically stirred at 25 °C for 1 h to prepare a transparent solution. Then, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) monomer (32.22 g, 0.1 mol) was added and dissolved in the above solution, and mechanically stirred at 70 °C for 18 h to obtain BTDA-APBIA. 20 -PI precursor solution, the solid content of the solution is 15 wt %;

[0112] (2) In a 20 mL flat-mouth glass bottle, add the BTDA-APBIA obtained in (1) above. 20 -PI precursor solution (1.67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / BTDA-APBIA 20 -PI (50:50) composite polymer precursor solution;

[0113] (3) The obtained PAA / BTDA-APBIA 20 The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature, treated at 60°C for 1 hour, and then vacuum treated at 120°C for at least 1 hour, and vacuum treated at 200°C for at least 10 minutes to complete the heat treatment process, and PAA / BTDA-APBIA was obtained. 20 -PI (50:50) composite polymer film (50um);

[0114] (4) Table 1 summarizes the PAA / BTDA-APBIA 20 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0115] The remaining application steps are the same as Example 1.

[0116] Example 12:

[0117] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, first dissolve p-PDA (8.65 g, 0.08 mol) and APBIA (4.48 g, 0.02 mol) in deionized water (242 g), then add 1.25 times the carboxylic acid equivalent of DMIZ (24.03 g, 0.25 mol) and mechanically stir at 25 ° C for 1 h to prepare a transparent solution. Then add 2,3,3',4'-biphenyltetracarboxylic dianhydride (α-BPDA) monomer (29.42 g, 0.1 mol) and dissolve it in the above solution. Mechanically stir at 70 ° C for 6-18 h to obtain α-BPDA-APBIA 20 -PI precursor solution, the solid content of the solution is 15 wt %;

[0118] (2) In a 20 mL flat-mouth glass bottle, add the α-BPDA-APBIA obtained in (1) above. 20 -PI precursor solution (1.67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 1 h to obtain PAA / α-BPDA-APBIA 20 -PI (50:50) composite polymer precursor solution;

[0119] (3) The obtained PAA / α-BPDA-APBIA 20 The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature, treated at 60°C for 1 h, then vacuum treated at 120°C for 1 h, and vacuum treated at 200°C for 30 min to complete the heat treatment process to obtain PAA / α-BPDA-APBIA 20 -PI (50:50) composite polymer film;

[0120] (4) Table 1 summarizes the PAA / α-BPDA-APBIA 20 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0121] The remaining application steps are the same as Example 1.

[0122] Example 13:

[0123] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, firstly, p-PDA (8.65 g, 0.08 mol) and APBIA (4.48 g, 0.02 mol) were dissolved in deionized water (277 g), and then 1.25 times the carboxylic acid equivalent of DMIZ (24.03 g, 0.25 mol) was added and mechanically stirred at 25 °C for 1 h to prepare a transparent solution. Then, 3,3,4,4-diphenylsulfone tetracarboxylic dianhydride (DSDA) monomer (35.82 g, 0.1 mol) was added and dissolved in the above solution, and mechanically stirred at 70 °C for 18 h to obtain DSDA-APBIA. 20 -PI precursor solution, the solid content of the solution is 15 wt %;

[0124] (2) In a 20 mL flat-mouth glass bottle, add the DSDA-APBIA 20 -PI precursor solution (1.67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 5 h to obtain PAA / DSDA-APBIA 20 -PI (50:50) composite polymer precursor solution;

[0125] (3) The obtained PAA / DSDA-APBIA 20 The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / DSDA-APBIA. 20 -PI (50:50) composite polymer film;

[0126] (4) Table 1 summarizes the PAA / DSDA-APBIA 20 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0127] The remaining application steps are the same as Example 1.

[0128] Example 14:

[0129] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, first dissolve p-PDA (8.65 g, 0.08 mol) and APBIA (4.48 g, 0.02 mol) in deionized water (186 g), then add DMIZ (24.03 g, 0.25 mol), and mechanically stir at 25 °C for 1 h to prepare a transparent solution. Then add cyclobutanetetracarboxylic dianhydride (CBDA) monomer (19.61 g, 0.1 mol) and dissolve it in the above solution. Mechanically stir at 70 °C for 18 h to obtain CBDA-APBIA. 20 -PI precursor solution, the solid content of the solution is 15 wt %;

[0130] (2) In a 20 mL flat-mouth glass bottle, add the DSDA-APBIA 20 -PI precursor solution (1..67 g) and PAA (0.25 g) were dissolved in deionized water (10 g) and magnetically stirred for 5 h to obtain PAA / CBDA-APBIA 20 -PI (50:50) composite polymer precursor solution;

[0131] (3) The obtained PAA / CBDA-APBIA 20 The precursor solution of the -PI (50:50) composite polymer was directly cast on a glass plate or a stainless steel plate, and a film was cast at room temperature. The film was treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The heat treatment process was completed at 200°C for 30 minutes to obtain PAA / CBDA-APBIA. 20 -PI (50:50) composite polymer film;

[0132] (4) Table 1 summarizes the PAA / CBDA-APBIA 20 Properties of precursor solutions and films of the PI (50:50) composite polymers.

[0133] The remaining application steps are the same as Example 1.

[0134] Comparative Example 1:

[0135] This example uses the PAA / APBIA of Example 6 above. 20 -PI (50:50) precursor solution was used as a comparative example; the remaining application steps were the same as in Example 1.

[0136] Comparative Example 2:

[0137] This example uses PAA (Aladdin, weight average molecular weight of 450,000) as a comparative example, and the remaining application steps are the same as Example 1.

[0138] Comparative Example 3:

[0139] This example uses commercially available sodium carboxymethyl cellulose (DAICEL, CMC-2200) as a comparative example, and the remaining application steps are the same as those of Example 1.

[0140] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0141] Table 1 data testing method:

[0142] 1) Intrinsic viscosity dL g-1 test method: prepare the test sample into a 5 mg / L solution and use an Ubbelohde viscometer to measure the solvent retention time t 0 / s and the residence time t / s of the test sample, and calculate the intrinsic viscosity according to the following formula:

[0143] ;

[0144] 2) Rotational viscosity Pa s test method: Tested using a rheometer at 50°C;

[0145] 3) Test method for glass transition temperature ℃: Prepare polyacrylic acid / polyimide composite film into 40mm The 8mm sample was loaded on a dynamic thermomechanical analyzer, and the measurement temperature range was 50-350°C, with a heating rate of 5°C / min. The glass transition temperature was obtained based on the changes in the storage modulus and loss modulus.

[0146] 4) Test method for elastic modulus Gpa elastic strength MPa elongation at break %: Prepare polyacrylic acid / polyimide composite film into 60mm The sample was 10 mm thick and loaded on a universal tensile testing machine with a tensile rate of 50 mm / min.

[0147] Table 1

[0148]

Claims

1. A composite water-based polymer binder with strong self-healing properties prepared based on hydrogen bonding, characterized in that: The binder is prepared based on hydrogen bonding, and its raw materials include water-soluble polyimide (APBIA-PI) with a benzimidazole structure and polyacrylic acid (PAA). After mechanical blending of PAA and APBIA-PI, a composite polymer binder PAA / APBIA-PI with reversible physical cross-linking can be formed.

2. The adhesive according to claim 1, characterized in that The water-soluble polyimide with a benzimidazole structure (APBIA-PI) is copolymerized by 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA), other diamine monomers (B), dianhydride monomers (A) and imidazole organic compounds (M). The specific structure of the water-soluble polyimide with a benzimidazole structure (APBIA-PI) is as follows: ; Among them, x+y=1, 0≤x≤1, 0≤y≤1; A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group; for example, A is at least one of the following structures: ; B represents at least one of the following groups: a divalent organic group of an aromatic diamine that does not contain fluorine and does not contain an amino group; a divalent organic group of an aliphatic diamine whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is at least one of the following structures: ; M is an imidazole organic compound, which reacts with the carboxyl group of polyamic acid to form a water-soluble polyamic acid salt, and its structural characteristics are as follows: ; Wherein, X1 to X4 represent a hydrogen atom or an alkane group having less than 5 carbon atoms.

3. The adhesive according to claim 2, characterized in that The polyacrylic acid (PAA) has a large number of carboxylic acid groups (on average, 1g of polymer molecules has more than 13.88 mmol of carboxylic acid groups), providing sites for interaction with imidazole; the weight average molecular weight of the polyacrylic acid is not less than 10,000 and not more than 1,000,000.

4. A method for preparing the adhesive according to claim 1, characterized in that: The steps include: (1) First, at room temperature, 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and one or more diamine monomers of the diamine monomer containing the B group are dissolved in deionized water, then at least one imidazole product of the imidazole organic compound M is added to the solution, and stirred for at least 1 hour to prepare a transparent solution, and then a dianhydride monomer containing the A group is added and dissolved in the aforementioned solution, the molar ratio of the dianhydride to the diamine monomer is 0.9-1.3:1, the solution concentration is controlled at 10-30wt%, and the molar ratio of the imidazole organic compound M to the dianhydride monomer containing the A group is 2.5 or more; (2) Under an inert gas environment, the mixture in step (1) is reacted for at least 6 hours to obtain a product having a certain viscosity (greater than 100 mPa at 25°C). s) a precursor solution of an aqueous imidazole-containing polyimide (APBIA-PI); (3) Dissolve the APBIA-PI precursor solution and PAA in deionized water at room temperature and mechanically stir for at least 1 h to obtain a PAA / APBIA-PI precursor solution.

5. The method according to claim 4, characterized in that The method further comprises the following steps: (4) Under vacuum, the obtained PAA / APBIA-PI precursor solution is treated at high temperature (>100°C) for at least 30 min to obtain PAA / APBIA-PI.

6. Use of the binder according to claim 1 in lithium ion batteries.

7. Use of the binder prepared by the method according to claim 4, characterized in that: As an electrode binder, used in lithium-ion batteries, the application comprises the following steps: 1) Electrode manufacturing step: the negative electrode active material, conductive agent, polyimide precursor solution and deionized water are mixed evenly to obtain a slurry, and the slurry is evenly coated on one side of the current collector; here, the solid content of the PAA / APBIA-PI precursor solution is higher than 1wt%, and the negative electrode active material loading is greater than 0.2mg·cm -2 ; 2) The coated electrode is placed in a forced air oven at 60-100°C for 1-3 hours and then transferred to a vacuum oven for treatment at a higher temperature (>100°C) for 0.5-12 hours to complete the preparation of the electrode with PAA / APBIA-PI as a binder; 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-12 mm on a manual slicer; the mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating; 4) Complete the installation of the lithium-ion battery buckle.

8. Use of the binder prepared by the method according to claim 4, characterized in that: For polyimide film, the application comprises the following steps: 1) The obtained PAA / APBIA-PI precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 60-100°C for 5-24h to form a film, and then vacuum dried at 80-120°C for 5-24h, and vacuum treated at 150°C-350°C for 1-12h to complete the imidization process, thereby obtaining a PAA / APBIA-PI composite polymer film.